Acupuncture for angina post percutaneous coronary intervention: a protocol for systematic review and meta-analysis - Xin Zhou; Yulan Ren; Wen Xie; Yanwei Li; Yongjun Yin; Yilan Wang (BMJ Open)
Introduction Ischaemic heart disease (IHD) is a pathological process characterised by a blockage or non-obstructive accumulation of atherosclerotic plaques in the epicardial arteries. Percutaneous coronary intervention (PCI) is widely used in clinical practice to treat IHD. However, angina post PCI (APPCI) impairs quality of life and portends a worse prognosis. Hence, an effective and safe treatment option remains an urgent need for patients with APPCI. In recent years, there has been an increasing body of clinical trials regarding the use of acupuncture for the prevention and treatment of APPCI, and the results have indicated it might be a promising therapeutic intervention. However, to our knowledge, the potential benefits of acupuncture for the prevention and treatment of APPCI to justify either their recommendation or their clinical role have not been evaluated.Methods and analysis PubMed, Embase, Cochrane Library, Web of Science Core Collection, Chinese Biomedical Database, Chinese National Knowledge Infrastructure, Wanfang Database and VIP Database will be searched from inception to 8 June 2024 without language restrictions. Two investigators will independently screen studies, extract data, assess the risk of bias from randomised controlled trials (RCTs) and assess the risk of bias. The third reviewer will arbitrate any disagreements. Data synthesis and analysis will be conducted using the RevMan V.5.4 software. Subgroup analyses, sensitivity analysis, meta-regression and bias reporting assessments will be performed if necessary and appropriate. Finally, the quality of evidence from RCTs will be assessed using the Grading of Recommendations Assessment, Development, and Evaluation System tool.Ethics and dissemination Ethical approval is unnecessary since no private or confidential patient data will be included. The systematic review will be published in peer-reviewed journals.PROSPERO registration number CRD42024562116.